Clinically Non-Functioning Pituitary Incidentaloma Presenting as Recurrent Episodes of Hypoglycemia - Nobian Andre; Marco Vidor; James Marcus; Teddy Ervano (PP PERKENI, 2025)
A pituitary adenoma is a tumor originating from the adenohypophysis. Pituitary adenomas are mostly discovered incidentally during radiological examinations performed for other purposes. Not all pituitary adenomas are functional. Non-functioning adenomas often present with symptoms due to mass effect and pituitary hormone deficiency. This case report presents a case of a 56-year-old man with type 2 diabetes mellitus who had an accidental finding of pituitary macroadenoma without overt hormone hypersecretion symptoms, but experienced recurrent hypoglycemia. Further investigation revealed low cortisol and insulin like growth hormone-1 levels, suggesting a Houssay phenomenon that leads to ‘resolution’ of diabetes due to hypopituitarism. Even in patients without overt symptoms of hormone hypersecretion, the possibility of subtle hypopituitarism due to tumor-induced pituitary dysfunction should not be overlooked. Patients with pituitary adenomas require evaluation by a multidisciplinary team involving endocrinology, neurosurgery, and ophthalmology.